A hydrophobic semiconducting metal–organic framework assembled from silver chalcogenide wires. Issue 14 (21st January 2020) - Wang, Jia-Yin; Li, Wen-Hua; Wei, Zhong; Zhang, Chong; Li, Ya-Hui; Dong, Xi-Yan; Xu, Gang; Zang, Shuang-Quan
Abstract : Silver chalcogenide wires are for the first time assembled into a rigid framework structure using a fluorinated carboxylate ligand, where electron transfer along Ag–S chains enables semi-conduction. Abstract : Silver chalcogenide wires are assembled for the first time using a linear fluorinated carboxylate ligand into a metal–organic framework (MOF) with multifunctional properties. Fluorinated ligands in the host framework endow the MOF with excellent hydrophobicity. More interestingly, it displays typical semiconductivity due to the ordered nanoarray of non-discrete helical (–Ag–S–) n chains.